1993
DOI: 10.1002/sia.740200518
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of plastics by plasma treatment and plasma polymerization and its effect on adhesion

Abstract: The adhesion between plasma-modified polyethylene (PE) and Merent polar polymers, as well as aluminium and steel, has been studied. The PE was modified by either oxygen plasma treatment or plasma polymerization of acrylic acid. The results show the importance of introducing polar groups on the surface of the non-polar PE in order to improve the adhesion to polar polymers as well as metals. Laminates made of plasma-modi6ed PE and polyamide 6 (PA-6) or poly(ethy1ene vinyl alcohol) (EVAL-G) showed failure in P A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Acrylic acid plasma polymerization and copolymerization was a subject of several papers [29][30][31][32][33][34][35][36]. Some authors claim that level of functionality and chemical structure retention in the deposit can be controlled by the plasma deposition power [36].…”
Section: Plasma Polymerization Of Acrylic Acid On the Psu Membrane Sumentioning
confidence: 99%
See 1 more Smart Citation
“…Acrylic acid plasma polymerization and copolymerization was a subject of several papers [29][30][31][32][33][34][35][36]. Some authors claim that level of functionality and chemical structure retention in the deposit can be controlled by the plasma deposition power [36].…”
Section: Plasma Polymerization Of Acrylic Acid On the Psu Membrane Sumentioning
confidence: 99%
“…Some authors claim that level of functionality and chemical structure retention in the deposit can be controlled by the plasma deposition power [36]. Low power plasma results in the film very similar to the conventional poly(acrylic acid) with respect to carboxyl groups presence, film wettability and other properties [30,32,35,36]. In such case the plasma polymerization could serve as an alternative way of introducing acidic group on the PSU membrane surface.…”
Section: Plasma Polymerization Of Acrylic Acid On the Psu Membrane Sumentioning
confidence: 99%
“…[61][62][63] However, surface treatments of thermoplastics were also found to be effective in creating composites. 64 Results from hydrogen and oxygen RF-plasma treatments of fi lter paper (open texture and free from low-molecular-weight materials) and grease-proof paper (closed texture and the presence of lowmolecular-weight compounds) indicated that hydrogen plasma environments reduce the cellulose surfaces and generate low molecular weight degradation products, whereas oxygen plasma exposure increases the relative surface oxygen content and improves adhesion (see Figure 10). 61 It was shown that reduction of cellulose surfaces does not infl uence the adhesion signifi cantly.…”
Section: Plasma Surface Modifi Cation In Cellulosic Fi Bre-based Compmentioning
confidence: 96%
“…The peel test is widely used to measure the adhesion strength of a metallized layer on the polymeric substrate [8,[11][12][13][14], particularly for the quantitative evaluation of the metal adhesion after modification of the chemical composition of the polymeric surface, for example by means of plasma pre-treatment [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%